Comparing native and non-native seed-isolated strains for drought resilience in maize (Zea mays L.) - Tatiana Gil; Inês Rebelo Romão; Joana do Carmo Gomes; Omar Vergara-Diaz; Lucas Amoroso Lopes de Carvalho; Andre Sousa; Flavia Kasa; Raquel Teixeira; Sara Mateus; Artūrs Katamadze; Daniel Guariz Pinheiro; Rubén Vicente; et al. (Plant Stress, 2024)
Maize, a vital crop for human nutrition, livestock, and industrial development, faces increasingly severe climatic conditions that hinder its production capacity along with other strategic crops. Novel treatments based on microorganisms have demonstrated efficiency in enhancing plant development and responding to stress. The use of bacteria isolated from seeds is a novel approach for biotreatment, as recent studies point to a co-evolution process for their presence in seeds. This approach hypothesize a pre-adaptation to its host, which may lead to increased efficiency. However, several aspects of this approach remain understudied. In this study, we aimed to evaluate the potential of native maize seed microbiota in comparison to that isolated from other species to mitigate drought stress. For this we characterized seedborne microbiota of a common productive maize variety in Portugal, to use it as biotreatment in other two varieties (sensitive and resistant to drought), selecting the strain Pseudomonas fulva MB as the most promising candidate. Stenotrophomonas maltophilia MS-M1 strain, isolated from wild alfalfa seeds and previously characterized as a drought-tolerant enhancer, served as a non-native control strain. According to the data, both varieties of maize demonstrated enhanced vegetative growth when treated with both individual strains, as well with the consortium, with an increase in plant height of 5–7 % in full and medium irrigation, and 50–55 % when not irrigated. This trend was also observed in plant weight, which increased by 13–23 %, even under no irrigation. In addition, production in both varieties was positively impacted by these treatments, based on the amount of grain produced (by weight). The drought-sensitive variety experienced a 17 % increase under full irrigation, while the most tolerant variety experienced a 25–40 % increase. Under medium irrigation level, the increase was about 15 % in both varieties, while a 100 % and 140 % increase was observed in each variety, respectively, when no irrigation was applied. The results suggest that native strain the P. fulva MB was slightly more efficient treatment, as it outperformed the non-native strain in terms of productivity in both varieties. However, the differences were not solid enough along all parameters to consistently asses such difference. The consortium treatment only showed better performance under full or medium irrigation conditions for some production traits. These findings support the use of seed microbiota as very efficient biotreatments, suggesting than even non-native strains have a remarkable beneficial impact (interspecific), expanding the possible of use of this kind of bioinoculants. Further test are required to optimize the use of seed-isolated strains as better adapted or tailor-made solutions for agriculture.